Fine mrtve djevojke - Matanić, Dalibor (Croatia : Alka film ; HRT Zagreb ; Patljak, Jozo, 2002)
Situated in contemporary Zagreb, the film centers on a young lesbian couple, Iva and Mare. They rent a shady flat next to the railway station, but soon realize that this seemingly quiet neighborhood is full of dark secrets and prejudices. Among their new neighbors are a sleazy gynecologist, a prostitute and a war veteran who regularly beats his wife. Still the worst of all seems to be their landlady Olga who constantly observes the new tenants, and when she realizes that two girls are lesbians, immediately gives them notice. Hearing this, Olga’s aggressive son Daniel, whom she pathologically adores, rapes Iva. In an emerging clash, in which literally the whole neighborhood is involved Danijel falls under a train and Marija is killed under suspicious circumstances. Up to this point, we learn about this story retrospectively, through the testimony of Iva, who is by now married and has a son who has just been kidnapped. She is telling her story to the police inspector assigned to the case, how Marija’s murder remained unsolved, and when Iva became pregnant with her new husband, Olga was convinced that the baby was her grandson and the illusion drove her into kidnapping. Eventually, the boy is rescued, while Iva’s secret remains safe from her husband.
Keywords: Fiction films